Предмет: Математика,
автор: Mlpoiuytrewqazxcvbn
Из равенства (4x-y+2)(x+3)-(x+y+3)(4x+2)+5xy+10x=0 выразите "y" через "x"
Ответы
Автор ответа:
1
Ответ:
y=2x
Пошаговое объяснение:
(4x^2+12x-xy-3y+2x+6)-(4x^2+2x+4xy+2y+12x+6) +5xy+10x=0;
4x^2+12x-xy-3y+2x+6-4x^2-2x-4xy-2y-12x-6+5xy+10x=0;
-5y+10x=0;
-5y=-10x;
y=10x/5=2x
Похожие вопросы
Предмет: Математика,
автор: ss0993832
Предмет: Английский язык,
автор: vlvdvdaclccdvlc
Предмет: Алгебра,
автор: toriteme503
Предмет: Математика,
автор: impaladdd
Предмет: Биология,
автор: Аноним